2016
DOI: 10.1089/ten.tec.2015.0383
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Dual Energy X-Ray Absorptiometry Analysis of Trabecular Bone-Rich Regions in Mice: Improved Precision, Accuracy, and Sensitivity for Assessing Longitudinal Bone Changes

Abstract: Trabecular bone is frequently studied in osteoporosis research because changes in trabecular bone are the most common cause of osteoporotic fractures. Dual energy X-ray absorptiometry (DXA) analysis specific to trabecular bone-rich regions is crucial to longitudinal osteoporosis research. The purpose of this study is to define a novel method for accurately analyzing trabecular bone-rich regions in mice via DXA. This method will be utilized to analyze scans obtained from the International Space Station in an up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…There was little overlap between those determined to be bone genes by the IMPC and those found by the BoneBase protocol (72). Given that whole body areal BMD obtained from DXA is largely a cortical and bone size driven phenotype (65) and that microCT can be used specifically to look only at the trabecular bone, this is not an unexpected finding. This is further supported by evidence that suggests that trabecular and cortical bone are controlled by independent genetic signals (7577).…”
Section: Phenotyped Mouse Modelsmentioning
confidence: 91%
See 2 more Smart Citations
“…There was little overlap between those determined to be bone genes by the IMPC and those found by the BoneBase protocol (72). Given that whole body areal BMD obtained from DXA is largely a cortical and bone size driven phenotype (65) and that microCT can be used specifically to look only at the trabecular bone, this is not an unexpected finding. This is further supported by evidence that suggests that trabecular and cortical bone are controlled by independent genetic signals (7577).…”
Section: Phenotyped Mouse Modelsmentioning
confidence: 91%
“…DXA BMD in a mouse is different than that collected usually for GWAS purposes in humans. Even with the superior resolution of the newer DXA machines, in mice, these instruments are not able to discriminate between cortical and trabecular regions of interest without specialized analysis (65). It has been estimated for long bones that three quarters of the bone mass is contributed by the cortical compartment primarily in the diaphyses (66).…”
Section: Phenotyped Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures from the left and right femurs from a single mouse were averaged together and reported as a single value within. As mice were not fasted as part of this study, vertebral measures were found to be unreliable due to the presence of food pockets ( Shi et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Images were analyzed by TrapHisto and OsteoidHisto 35 . On the day of sacrifice, BMD was also measured in intact mice 36 . Frozen bone sections were incubated for 4 min at room temperature in Alkaline Phosphatase Substrate Solution ImmPACT Vector Red (Vector Laboratories).…”
Section: Skeletal Phenotypingmentioning
confidence: 99%